2016
DOI: 10.1111/jgh.13171
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease on the risk of acute pancreatitis: A population‐based cohort study

Abstract: IBD is a risk factor for acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 18 publications
1
37
0
4
Order By: Relevance
“…UC patients are reported to be at an increased risk of developing acute pancreatitis compared to the general population[31]. According to a study performed in 2003, the annual incidence of acute pancreatitis in South Korea was 19.4 per 100000 persons[32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UC patients are reported to be at an increased risk of developing acute pancreatitis compared to the general population[31]. According to a study performed in 2003, the annual incidence of acute pancreatitis in South Korea was 19.4 per 100000 persons[32].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that two cases of AIP occurred before the diagnosis of UC. There have been several reports of AIP occurring before the diagnosis of CD[31,32,39,40], but to the best of our knowledge, there have been no reports of AIP that preceded UC. Our results suggest that patients with repeated episodes of unexplained acute pancreatitis should be evaluated for inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…10 AP may be the initial extraintestinal manifestation of a systemic illness such as inflammatory bowel disease. A study conducted by Chen et al 11 found that AP preceded the diagnosis of IBD in more than 2% of patients.…”
Section: When To Suspect Pancreatitismentioning
confidence: 99%
“…Уровень заболеваемости составил 4,3% и 2,1% соответствен но [49]. Кроме того, в популяционном когортном ис следовании на Тайване общая частота ОП была в 3,56 раза выше у пациентов с ВЗК по сравнению с пациентами без ВЗК [11]. Предполагают, что ВЗК, проявляющийся ОП, более распространен среди пе диатрической популяции с ВЗК, чем у взрослых с ВЗК.…”
Section: опunclassified
“…Этиология В патогенез ОП при ВЗК включен широкий спектр механизмов (табл. 2, 3 [5,11,49,75]). Желчные кам ни и лекарственные препараты являются наиболее распространенными причинами ОП при ВЗК; эндо скопическая ретроградная холангиопанкреатогра фия, баллонная энтероскопия, гиперкальциемия и гипертриглицеридемия как причины ОП встреча ются реже [46].…”
Section: опunclassified